Investigating Flexural Behaviour of Prestressed Concrete Girders Cast by Fibre-Reinforced Concrete. (1st April 2019) - Rashid, Muhammad U.; Qureshi, Liaqat A.; Tahir, Muhammad F.
Abstract : The main objective of this research was to investigate the effect of adding polypropylene and steel fibres on flexural behaviour of prestressed concrete girders. Although the construction industry is frequently using prestressed concrete to increase the load-carrying capacity of structures, it can be further enhanced by using fibres. In this paper, experimental work was carried out to encourage the construction industry in utilizing fibres in prestressed concrete members to improve the mechanical properties of these members. As past investigations on fibre-reinforced prestressed beams were limited, the present work was done on small-scale fibre-reinforced I-shaped prestressed concrete girders. Six small-scale prestressed concrete girders were cast comprising a control girder, a hybrid girder, two girders with varying percentages of steel fibres, and two girders with varying percentages of polypropylene fibres. These girders were tested by centre point loading up to failure. It was concluded that, by the addition of small volume fraction of fibres, not only the ductility but also the tensile strength and flexural strength of FRC girders could be improved. It also altered the failure pattern positively by enhancing large strains in concrete and steel. Steel fibre-reinforced concrete showed higher energy absorption and deflection at ultimate loads in comparison to other specimens.